Bank efficiency and the efficient market hypothesis: the case for bank stock prices in KLSE - Habibullah, Muzafar Shah; Makmur, Muhd Iqbal; Wan Ngah, Wan Azman Saini; Radam, Alias; Ong, Hway Boon (Giordano Dell-Amore Foundation, 2005)
The purpose of the present study is to investigate the informationally efficient market hypothesis of the bank stock prices listed at the KLSE with respect to bank's operating efficiency. In this study, using data envelopment analysis technique, we compute the overall technical efficiency and decomposed it into pure technical efficiency, scale efficiency and congestion efficiency. We found out that the percentage changes in the prices of the bank shares at the KLSE reflect percentage changes in the overall technical efficiency but not to the pure technical, scale and congestion efficiencies scores. We therefore, conclude that the Malaysia's bank stock return is price inefficient in the semi-strong form sense.